Media Kartu Enaktif, Ikonik, dan Simbolik (EIS) untuk Meningkatkan Kemampuan Mengenal Bilangan Anak Usia 4–5 Tahun - Suparti, Suparti; Kristiana, Dian; Fatimah, Siti (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study aimed to improve the number recognition skills of children aged 4–5 years through the use of Enactive, Iconic, and Symbolic (EIS) card media at TK PKK Sobo Desa Gedangan Kecamatan Ngrayun Kabupaten Ponorogo. The study was motivated by the low level of children's number recognition abilities, as indicated by difficulties in sequencing numbers, identifying number symbols, counting objects, and matching number symbols with corresponding quantities. This research employed a Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, consisting of two cycles: planning, action, observation, and reflection. The participants were 21 children in Group A, aged 4–5 years. Data were collected through observation, documentation, and field notes, while data analysis was conducted using both quantitative and qualitative descriptive techniques. The results revealed that the implementation of EIS card media significantly improved children's number recognition skills. In the pre-cycle stage, only 24% of the children achieved the categories of Developing as Expected (DE) and Very Well Developed (VWD). Following the intervention in Cycle I, the percentage increased to 62%, and further improved to 86% in Cycle II, exceeding the predetermined success criterion of 80%. This improvement occurred because EIS card media provided a structured learning experience that progressed from concrete activities to visual representations and finally to symbolic understanding, in accordance with Bruner’s learning theory. Therefore, it can be concluded that Enactive, Iconic, and Symbolic (EIS) card media are effective in enhancing number recognition skills among children aged 4–5 years while creating a more active, engaging, and meaningful learning environment.